The Pivotal Role of Islamic Religious Education Teachers in Fostering Moral Development among Senior High School Students: Insights from Indonesian Case Studies - Yogi Rodini; Iskandar Mirza (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering students' morals in the digital era through a comparative case study at SMA Wanayasa (state) and SMK Ma'arif 4 Kebumen (private Islamic). Using a qualitative approach and case study design, data were collected through participant observation, in-depth interviews with 12 informants (teachers, students, and the principal), and analysis of school policy documents. The results of the study revealed three key findings: (1) PAI teachers play a dual role as educators and digital curators who filter negative content while developing platform-based materials such as educational TikTok and the "MoralTrack" application; (2) Technology integration increased student participation by 55%, but created a paradox between increased critical awareness (34% of students) and mental exhaustion due to content overdose (22%); (3) Significant differences were found in teachers' digital competence (62% in SMK vs. 35% in SMA) and achievement of Kohlberg's moral development stages (68% of SMK students reached the conventional stage vs. 52% in SMA), influenced by the intensity of digital case-based moral dilemma discussions. This study concludes that effective moral development in the digital era requires synergy between teachers' digital literacy, school-parent collaboration through a parental engagement dashboard, and the revitalization of the Islamic Religious Education (PAI) curriculum based on algorithmic moral vulnerability. These findings revise the theory of role models (uswah hasanah) by incorporating virtual mentorship and data-driven moral assessment.